72 VITAMIN D LEVELS AND SUPPLEMENTATION IN FRAIL OLDER ADULTS PRESENTING TO AN IRISH LEVEL 5 EMERGENCY DEPARTMENT. (18th November 2021) - Pender, C; Dillon, L; Byrne, C; Magner, S; Ryan, A; Murphy, A; Carribine, N; Laguna, R; Malomo, K
Abstract: Background: The Department of Health published new guidance in November 2020 'Vitamin D advice for people aged 65 and older' which states that all adults >65 years should be supplemented with 15micrograms of Vitamin D daily. TILDA research states that 55.5% of adults >65 years have either insufficient or deficient vitamin D levels in winter (TILDA 2020). The Frailty Intervention Team (FIT) assess frail adults >65 years in the Emergency Department using medication review and Comprehensive Geriatric Assessment (CGA) to identify vitamin D supplementation. The audit aim is to determine if the new guideline is being implemented. Methods: All patients who had a medicine reconciliation completed by the FIT Pharmacist in January 2021 were included in a retrospective audit. Patients were identified from the pharmacists worklist. Data was collected from a Hospital Clinical System using an excel data collection sheet. The data recorded included: Variable Indicative of Placement risk (VIP), Age, Sex, Rockwood Clinical Frailty Score (CFS), serum vitamin D level, date of last serum vitamin D level and vitamin D supplementation. Results: The FIT Pharmacist completed 60 medicine reconciliations in January 2021. The mean age (+/-SD) was 81.9 (+/− 7.9) years. The male to female ratio was 1:2.3. The median CFS was 5 (mildly/moderately frail) with an IQR of 2. 70% (n = 42) were prescribed vitamin D. Of those 92% (n = 39) were prescribed a supplement containing at least 15micrograms of vitamin D. 85% (n = 51) had a vitamin D level reported in the preceding 6 years. 76% (n = 39) had sufficient vitamin D levels (>50 nmol/L). 21% (n = 11) had insufficient or deficient vitamin D levels (<50 nmol/L). Conclusion: The new guideline was implemented in 65% (n = 39) of frail patients >65 years. The rate of vitamin D insufficiency in this cohort was lower than TILDA research suggests.